Combining therapeutic hypothermia and emergent coronary angiography in out-of-hospital cardiac arrest survivors: Optimal post-arrest care for the best patient. Issue 6 (December 2015) - Casella, Gianni; Carinci, Valeria; Cavallo, Piergiorgio; Guastaroba, Paolo; Pavesi, Pier C; Pallotti, Maria G; Sangiorgio, Pietro; Barbato, Gaetano; Coniglio, Carlo; Iarussi, Bruno; Gordini, Giovanni; Di Pasquale, Giuseppe
Background: Aggressive post-resuscitation care, in particular combining mild therapeutic hypothermia (MTH) with early coronary angiography (CAG) and percutaneous coronary intervention (PCI), may improve prognosis after out-of-hospital cardiac arrest (OHCA). Objectives: The study aims to assess the value of immediate CAG or PCI in comatose survivors after OHCA treated with MTH and their association with outcomes. Methods: Observational, prospective analysis of all comatose, resuscitated patients treated with MTH at a tertiary centre and undergoing CAG or PCI ≤6 hours after OHCA, or non-invasively managed. Primary outcomes were 30-day and 1-year survival. Results: From March 2004–December 2012, 141 (51%) out of 278 comatose patients after cardiac OHCA were treated with MTH (median age: 64.5 (interquartile range 55–73) years, males: 67%, first shockable rhythm: 70%, witnessed OHCA: 94%, interval OHCA-resuscitation≤20 min: 81%). Ninety-seven patients (69%) underwent early CAG, and 45 (32%) of them PCI. Patients undergoing CAG or PCI had a more favourable risk profile than subjects non-invasively managed. PCI treated patients had more bleedings, but no stent thrombosis occurred. Thirty-day and one-year unadjusted total mortality rates were 50% and 72% for non-invasively managed patients, 26% and 38.7% for patients submitted only to CAG and 32% and 36.6% for patients treated with PCI ( p =0.0435 for early death, and p <0.0001 for one-year mortality, respectively). However, a propensity-matched score analysis did not confirm the survival advantage of invasive management ( p =0.093). At multivariable analysis, clinical and OHCA-related variables as well as CAG, but not PCI, were associated with outcomes. Conclusions: Comatose patients cooled after OHCA and submitted to emergency CAG or PCI are a favourable outcome population that receives optimal post-arrest care.